Rancangan Acak Kelompok Lengkap ( RAKL ) Pada Pengaruh Harga Barang Dan Jasa Terhadap Inflasi - Murniati, Wahyuning (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2017)
One of things that influence inflation is the price of goods and services. In previous research, researcher calculate the inflation with Laspayers methods and generate 71,7% as correlation value. It is still not enough to make conclusion of this case because there is a lot of research that explain about inflation is influenced by many things. Therefore, this research apply Rancangan Acak Kelompok Lengkap (RAKL) to analyze the influence of the price of goods and services against inflation. The analysis process use Minitab software with inflation value as variable. The result of research explain that = 2,89 with = 5% so that means is rejected then it is true to conclude that the price of goods and services influce the inflasion